First Traces to Writing Academically: The Crafts of my Third Semester Students - RAMOS HOLGUÍN, BERTHA (Universidad Pedagógica y Tecnológica de Colombia, 2022)
The essays that follow were part of a Reading and Writing Workshop that took place during the first semester of 2021 with students who are enrolled in a Modern Languages Program with emphasis in English at Universidad Pedagógica y Tecnológica de Colombia. These students were in their third semester, and this was the first time they were asked to start writing following some academic parameters.